Regenerative Braking System For Through-The Road Parallel Hydraulic Hybrid Vehicle - Kumar, Denesh Kumar Siva (Universiti Sains Malaysia, 2021)
The hydraulic hybrid parallel architecture could be the key to tackle the low attainability rate of efficient hybrid vehicles. The design is a through-the-road configuration under the parallel architecture of a Hydraulic Hybrid vehicle. An Arduino rule-based control strategy system for the through-the-road hydraulic hybrid regenerative braking system on the prototype vehicle was developed to minimize vehicle fuel consumption. The dynamic programming was used to extract graphs and data from the vehicle's drive cycle as the reference to build the rule-based control strategy. Based on the results obtained the rule-based control strategy was developed using the Arduino microcontroller. The controlled conditions allow the pump of the regenerative braking system to function within its capabilities while also maximizing the usage of regenerative braking throughout the whole drive cycle.